2014
DOI: 10.3352/jeehp.2014.11.30
|View full text |Cite
|
Sign up to set email alerts
|

Learning style preferences of nursing students at two universities in Iran and Malaysia

Abstract: Purpose:Learning style preferences vary within the nursing field and there is no consensus on a predominant learning style preference in nursing students. The current study compared the learning style preferences of nursing students at two universities in Iran and Malaysia. Methods:A purposive sampling method was used to collect data from the two study populations. Data were collected using the Learning Style Scale (LSS), which is a valid and reliable inventory. The LSS consists of 22 items with five subscales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Items and definitions of LS provided by other scales were also compared and streamlined for similarities with the LS in the LSS in an effort to shape a rich discussion for this study. The study determined that most of the students identified themselves as perceptive learners, which may be similar to the results of previous studies using other LSS 25,48–50 . This finding suggests that the students in this study best learned with the optimal use of their five senses and understood better via direct observation and hands‐on experience 50–52 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Items and definitions of LS provided by other scales were also compared and streamlined for similarities with the LS in the LSS in an effort to shape a rich discussion for this study. The study determined that most of the students identified themselves as perceptive learners, which may be similar to the results of previous studies using other LSS 25,48–50 . This finding suggests that the students in this study best learned with the optimal use of their five senses and understood better via direct observation and hands‐on experience 50–52 .…”
Section: Discussionsupporting
confidence: 86%
“…The study determined that most of the students identified themselves as perceptive learners, which may be similar to the results of previous studies using other LSS 25,48–50 . This finding suggests that the students in this study best learned with the optimal use of their five senses and understood better via direct observation and hands‐on experience 50–52 . Conversely, the lowest‐rated LS was the sociable LS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result is similar to a randomized controlled study pointing out that the matched learning style teaching method can reduce the number of wrong attempts, but it is not statistically significant [ 50 ]. However, the learning style is a dynamic change [ 27 ], and different countries or education systems may have different learning style preferences [ 51 ]. For example, Australian nursing masters degree graduate students tend to be kinaesthetic [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imaginative learners create a mental picture of what they read, listen, watch, and study. They are whole-brain learners, which refers to the ability to integrate the right-brain and left-brain functions in learning situations [ 14 ]. The MON index refers to pride and stability versus humility, flexibility, and adaptability to changing circumstances.…”
Section: Discussionmentioning
confidence: 99%